Immobilization of choline chloride: urea onto mesoporous silica for carbon dioxide capture - Zaitun Ghazali; Nur Hasyareeda Hassan; Mohd Ambar Yarmo; Teh, Lee Peng; Rizafizah Othaman (Penerbit Universiti Kebangsaan Malaysia, 2019)
A green composite adsorbent based on mesoporous silica-gel (SG) and deep eutectic solvent (DES) mixture of choline chloride-urea (ChCl:U) was synthesized as an alternative for carbon dioxide (CO2) adsorption. The composite adsorbent was prepared by wet impregnation technique with various ChCl:U (mole ratio 1:2) content in SG at 5-15% (w/w). Fourier transform infrared attenuated total reflectance (ATR-FTIR) results showed successful impregnation of ChCl:U into SG with the presence of C=O carbonyl amide group stretching, N-H scissoring bending, CH2 bending and C-N stretching peaks. Thermal degradation of the adsorbent started with urea at 130°C followed by ChCl at 300°C. Meanwhile, nitrogen physisorption demonstrated a decrease in specific surface areas of the sorbents with increasing ChCl:U weight percentage due to the blockage of micropores by ChCl:U. The optimum CO2 adsorption capacity of 22.3 mg/g was achieved by 10%ChCl:U/SG200, which was higher than the immobilised SG200, hence making it relevant to become a green and economical adsorbent for CO2 capture.